Plant secondary metabolites extracted from Acorus calamus rhizome from Western Ghats, India and repellent activity on Sitophilus oryzae. (January 2022) - Elshikh, Mohamed S.; Rani, E.; Al Farraj, Dunia A.; Al-Hemaid, Fahad M.A.; Abdel Gawwad, Mohamed R.; Jeba Malar, T.R.J.; Dyona, L.; Vijayaraghavan, P.
Abstract: Medicinal plants are widely used to treat various ailments and Acorus calamus L. is one of the medicinal plants has ethnomedicinal significance. The rhizome of A. calamus was used for the extraction of phytochemicals using various solvent. The methanol extract showed the presence of flavonoids, alkaloids, phenolic compounds, tannins, steroids, saponins, glycosides and terpenoids. Biological study reported higher antimicrobial array for methanolic extract of A. calamus than other solvent extracts. Fourier Transform Infrared Spectroscopy analysis revealed the presence of alcohol, alkenes, carbonyl, aromatic, amine, methylene, venyl, phenyl, ether, cyclic ether, aromatic cyclic ether, and primary amines. Gas chromatography - mass spectrometry analysis revealed the presence of compounds such as asarone, n-hexadecanoic acid, 9, 15-octadecadienoic acid, methyl ester, (z, z)- and 9, 12-octadecadienoic acid (z, z). The methanolic extract of A. calamus was highly effective against bacteria such as, S. epidermis (5 μg/mL), P. vulgaris (5 μg/mL) and B. cereus (5 μg/mL). A. calamus extract was active against the tested Sitophilus oryzae, the insecticidal activity was dose dependence, and activity increased with higher doses and increased with incubation times. At 125, 250, 375, 500, 625 and 750 μg/cm 2 concentration, the insecticidal repellent activity was 13.8 ± 1.4%, 17.4 ± 2.3%, 22.3 ± 1.7%, 31.8 ± 2.6%, 44.1 ± 1.3%, and 44.2 ± 2.4, respectively after 24 h incubation. This study has demonstrated that methanolic rhizome extracts of A. calamus has significant antimicrobial, anti-biofilm and insecticidal activity against pathogenic plant bacterial pathogens and insect pests, it could be of high agricultural and pharmacological value.